2018
DOI: 10.1021/acsami.8b05314
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Tissue-Adhesive Hydrogel Based on the Polydopamine–Chondroitin Sulfate Complex for Growth-Factor-Free Cartilage Regeneration

Abstract: Glycosaminoglycan-based hydrogels are widely used for cartilage repair because glycosaminoglycans are the main component of the cartilage extracellular matrix and can maintain chondrocyte functions. However, most of the glycosaminoglycan-based hydrogels are negatively charged and cell-repellant, and they cannot host cells or favor tissue regeneration. Inspired by mussel chemistry, we designed a polydopamine-chondroitin sulfate-polyacrylamide (PDA-CS-PAM) hydrogel with tissue adhesiveness and super mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
192
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(198 citation statements)
references
References 51 publications
(88 reference statements)
6
192
0
Order By: Relevance
“…Direct addition of the CaCl 2 solution results in the rapid reaction between Ca 2+ and the guluronate blocks of alginate chains, which does not favor uniform gel formation and significantly affects the hydrogel properties. Moreover, the increased adhesiveness of BG/OSA might also be partially explained by the interlock effect, in which a rougher surface and a more viscous adhesive enable easier fluid penetration, producing more mechanical interlock joints and hence better adhesion 16,17 . All of this evidence demonstrated that BG played a multifunctional role in the BG/OSA composite hydrogel due to its unique dualadhesive property, which was not only adhesive to tissues but also to implantable materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct addition of the CaCl 2 solution results in the rapid reaction between Ca 2+ and the guluronate blocks of alginate chains, which does not favor uniform gel formation and significantly affects the hydrogel properties. Moreover, the increased adhesiveness of BG/OSA might also be partially explained by the interlock effect, in which a rougher surface and a more viscous adhesive enable easier fluid penetration, producing more mechanical interlock joints and hence better adhesion 16,17 . All of this evidence demonstrated that BG played a multifunctional role in the BG/OSA composite hydrogel due to its unique dualadhesive property, which was not only adhesive to tissues but also to implantable materials.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive strengths of the hydrogels on the implant materials were also measured by lap-shear strength tests as reported in dry conditions 17 . Some commonly used implant materials, including silicone, titanium alloy, tricalcium phosphate (TCP), and porous TCP, were cut into strips of size 10 mm × 10 mm.…”
Section: Characterization Of the Adhesiveness Of The Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has focused on the control of material properties of these systems by changing the chemical components, which simultaneously varied ECM adhesive ability or mechanics, making them become possible to regulate cell behavior and meet the requirement of cartilage repair (Benmassaoud, Gultian, DiCerbo, & Vega, 2019). Compared with bare chondroitin sulfate (CS), mussel-inspired tissue adhesive hydrogel based on polydopamine-CS complex was more effective in exerting its functions on adhered cells to upregulate chondrogenic differentiation (Han et al, 2018). Besides, polymeric scaffolds modified with arginine-glycine-aspartic acid (RGD) adhesion ligands have been used to enhance cell-matrix interaction and influence the differentiation of stem cells (Lee, Kim, & Lee, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from non-degradable adhesives [1], most biocompatible and biodegradable tissue adhesives utilize crosslinking mechanisms inspired by natural (marine) adhesives. The most common approach to creating adhesion is to incorporate a modified amino acid, L-DOPA (e.g., as a pendant group, onto a polymer) [2,3]. Coacervation and nanoscale electrostatic interactions are also sufficient to create relatively strong tissue adhesion [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%